2005
DOI: 10.1890/04-1621
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of Alternative Stable States in the Southern Boreal Forest, Québec, Canada

Abstract: The southernmost spruce–lichen woodlands in the Parc des Grands‐Jardins, Québec, Canada, are situated 500 km south of their usual range in the northern lichen woodland zone. Their co‐occurrence within a spruce–moss forest matrix suggests the existence of alternative stable states. We investigate the possibility of these spruce–lichen woodlands as an alternative stable state along with the factors contributing to their origin and spatiotemporal distribution. Analysis of plant macrofossils, charcoal, head capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(196 citation statements)
references
References 85 publications
8
176
1
11
Order By: Relevance
“…In fire-prone ecosystems, this could result in a similar interaction as described here. In the boreal forests of Canada, a strong correlation between insect outbreaks, fire, and subsequent long-term forest loss has been demonstrated in a historical study (Jasinski and Payette 2005), however mechanisms for the direct interaction are lacking. This study presents one potential means by which insects and fire could interact to produce longlasting compositional change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fire-prone ecosystems, this could result in a similar interaction as described here. In the boreal forests of Canada, a strong correlation between insect outbreaks, fire, and subsequent long-term forest loss has been demonstrated in a historical study (Jasinski and Payette 2005), however mechanisms for the direct interaction are lacking. This study presents one potential means by which insects and fire could interact to produce longlasting compositional change.…”
Section: Discussionmentioning
confidence: 99%
“…Forest ecosystems are characterized by long turnover times of dominant organisms and protracted periods of slow change, thus it is difficult to demonstrate a true change in the dominant cover. Dramatic changes to forest ecosystems may result from disturbance events (Frelich and Reich 1998), and some studies have shown shifts in cover types as a result of multiple disturbances/stressors (Jasinski andPayette 2005, Johnstone et al 2010). Several studies have demonstrated alternate stable states exist in the Rocky Mountain subalpine.…”
Section: Implications Of Exceeding Resiliencementioning
confidence: 99%
“…Similarly, disturbances may trigger rapid changes in environmental conditions that exceed a species' tolerance limits for re-establishment (Astrom et al 2007). In cases where future composition is strongly determined by initial patterns of community assembly, factors that influence patterns of post-disturbance recruitment play a key role in mediating between alternative stable states of community composition (Jasinski andPayette 2005, Baskett andSalomon 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. While each type has specific impacts on forest composition and dynamics, biogeochemical cycling and numerous ecological processes, there is an increasing recognition that the interaction of these types of disturbance can also have dramatic long-term effects on the ecosystem's structure and functioning [3,4].…”
Section: Introductionmentioning
confidence: 99%